2021
DOI: 10.1039/d1fo02563e
|View full text |Cite
|
Sign up to set email alerts
|

Distinct fermentation of human milk oligosaccharides 3-FL and LNT2 and GOS/inulin by infant gut microbiota and impact on adhesion ofLactobacillus plantarumWCFS1 to gut epithelial cells

Abstract: Fermentation of hMOs 3-FL and LNT2 by infant gut microbiota is structure dependent and different from the commonly applied GOS/inulin, and the fermentation digesta may lead to differential potencies to stimulate the commensal bacteria colonizaiton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…The effects of probiotics on the bacterial composition of the gut of healthy animals have also been relatively poorly studied. However, there have been studies that show the effectiveness of the use of probiotic supplements for preventive purposes [ 20 , 21 , 22 , 23 ]. For example, Yang et al showed that the combination of Cochlearius cochlearium and L. acidophilus has beneficial effects on body weight control and glucose homeostasis in high-fat DIO mice [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of probiotics on the bacterial composition of the gut of healthy animals have also been relatively poorly studied. However, there have been studies that show the effectiveness of the use of probiotic supplements for preventive purposes [ 20 , 21 , 22 , 23 ]. For example, Yang et al showed that the combination of Cochlearius cochlearium and L. acidophilus has beneficial effects on body weight control and glucose homeostasis in high-fat DIO mice [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…65 In the case of inulin, for example, fermentation of inulin increases the ability of lactobacilli to adhere, and this selection for specific functions of lactobacilli may be associated with an increased prevalence of some differential COGs. 66…”
Section: Discussionmentioning
confidence: 99%
“…65 In the case of inulin, for example, fermentation of inulin increases the ability of lactobacilli to adhere, and this selection for specific functions of lactobacilli may be associated with an increased prevalence of some differential COGs. 66 Lactobacilli associated with vegetarian diets showed a higher prevalence of genes with the highest number of differ-ential COGs in the [L] category, which includes DNA polymerase, DNA methylase and DNA methyltransferase. DNA methylation is widespread in bacteria and is a potent type of bacterial gene regulation that protects the host genome from damage.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Fucosylated and nonfucosylated neutral HMOs yielded more lactate, as compared to the sialylated HMOs . Lacto- N -triaose II specifically induced succinic acid production, and succinic acid triggered anti-inflammatory immune reactions …”
Section: Hmos Modulate Gut Microbiota and Produce Intestinal Metabolitesmentioning
confidence: 96%
“…208 Lacto-N-triaose II specifically induced succinic acid production, and succinic acid triggered anti-inflammatory immune reactions. 209…”
Section: ■ Hmos Modulate Gut Microbiota and Produce Intestinal Metabo...mentioning
confidence: 99%